Degradation Studies on Lithium Iron Phosphate - Graphite Cells. The Effect of Dissimilar Charging – Discharging Temperatures. (20th June 2017) - Ruiz, V.; Kriston, A.; Adanouj, I.; Destro, M.; Fontana, D.; Pfrang, A.
Graphical abstract: Fitted (surface) and measured degradation rates (dots) in the charge – discharge temperature space obtained from the reference cycles (R 2 = 0.92), where n is the number of cycles. Color code indicates red as conditions with a lower degradation rate and blue as conditions with a higher degradation rate. Highlights: Charge and discharge temperature affects differently ageing of LFP-graphite cells Degradation rate shows quadratic relationship with Tc and linear with Td Degradation rate presents a minimum when charge temperature is +15 °C Cycling in the range from -20 °C to +15 °C imposes almost no degradation Cycling at Tc = +30 °C and Td = -5 °C produces the highest degradation rate Abstract: This work presents a systematic evaluation of the effect of dissimilar charging / discharging temperatures on the long-term performance of lithium iron phosphate / graphite based cells by using multi-factor analysis of variance. Specifically, the degradation of prototype pouch cells is presented in a range of charging and discharging temperatures from -20 °C to +30 °C, counting a total of 10 temperature combinations. In this manner, not only the effect of charging and discharging temperatures was analyzed, but also the correlations between them. Fitting of the data showed a quadratic relationship of degradation rate with charging temperature, a linear relationship with discharging temperature and a correlation between charging and discharging temperature. Cycling at the charge/discharge temperatures (+30 °C, -5 °C) produced the highest degradation rate, whereas cycling in the range from -20 °C to +15 °C, in various charge/discharge temperature combinations, created almost no degradation. It was also found that when Tc≅ 15 °C the degradation rate is independent of Td . When Tc < +15 °C, the higher degradation occurs at higher Td and at Tc > +15 °C lower degradation occurs at higher Td .